2021
DOI: 10.3389/fcimb.2021.634780
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gut Microbiota and Microbiota-Related Metabolites on Hyperlipidemia

Abstract: Hyperlipidemia, defined as the presence of excess fat or lipids in the blood, has been considered as a high-risk factor and key indicator of many metabolic diseases. The gut microbiota has been reported playing a vital role in regulating host lipid metabolism. The pathogenic role of gut microbiota in the development of hyperlipidemia has been revealed through fecal microbiota transplantation experiment to germ-free mice. The effector mechanism of microbiota-related metabolites such as bile acids, lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 156 publications
(163 reference statements)
2
89
0
Order By: Relevance
“…Moreover, other gut-microbiota metabolites such as lipopolysaccharide (LPS), long-chain fatty acid and bile acids (BAs) have also been linked to the MetS traits. LPS could induce low-grade inflammation, which features obesity and insulin resistance [ 119 ]. Another report showed that long chain fatty acids derived by gut microbes could be one of the mechanisms implicated in the anti-inflammatory properties of probiotics [ 120 ].…”
Section: Gut Microbiota and Mets Of Developmental Originsmentioning
confidence: 99%
“…Moreover, other gut-microbiota metabolites such as lipopolysaccharide (LPS), long-chain fatty acid and bile acids (BAs) have also been linked to the MetS traits. LPS could induce low-grade inflammation, which features obesity and insulin resistance [ 119 ]. Another report showed that long chain fatty acids derived by gut microbes could be one of the mechanisms implicated in the anti-inflammatory properties of probiotics [ 120 ].…”
Section: Gut Microbiota and Mets Of Developmental Originsmentioning
confidence: 99%
“…Gut microbiota is composed of various microorganisms, such as bacteria, viruses and fungi in the intestine, and their living environment, which affect the physiological functions and pathological changes of host cells ( Chen et al., 2021 ). The intestinal microbiota has been taken attention increasingly because of its crucial roles in human immunity, metabolism, endocrine, neurodegeneration and other physiological processes ( Michaudel and Sokol, 2020 ; Jia et al., 2021 ; Murciano-Brea et al., 2021 ; Xu et al., 2020 ). Patients with respiratory diseases, including allergic asthma, acute lung injury, pulmonary fibrosis, and bacterial infection, often have drastic changes of the proportion and function of intestinal and lung microbiota ( Zhou et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GM after bariatric surgery (BS) appears to impact appetite regulation and satiety energy balance, thereby affecting weight control and metabolism ( Martinou et al, 2022 ). Moreover, there is growing evidence that several natural herbs can effectively improve dyslipidemia by regulating gut flora ( Jia et al, 2021 ), though their metabolic benefits and mechanisms are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%